(untitled) (Journal of Engineering, 2014)
A new concrete rheometer is introduced including its innovation, actual design, working rules, calibration, and reliability. A modified design of Tattersall two-point device is created. Some of components are purchased from local and foreign markets, while other components and the manufacturing process are locally fabricated. The matching viscosity method of determining the mixer viscometer constants is demonstrated and followed to relate torque and rotational speed to yield stress and viscosity (Bingham parameters). The calibration procedures and its calculation are explained. Water is used as a Newtonian fluid, while; cement paste (cement + water) with w/c ratio equal to (0.442) is used as a non-Newtonian fluid. The cement paste is tested in “Petroleum Research and Development Center” by “OFITE Model 800 Viscometer”. In order to verify the reliability of the new rheometer, an Artificial Neural Network (ANN) model with a well selected bank of data is constructed; and (16) Mixes of Self Compacting Concrete (SCC) are constructed, mixed and tested by the new Rheometer. The results from model (predicted) and those from the experimental work (measured) were found to have very good degrees of correlation and matching, which indicates that the new rheometer can be reliable.